Trends and health impacts of major urban air pollutants in Kazakhstan. (2nd November 2019) - Kerimray, Aiymgul; Kenessov, Bulat; Karaca, Ferhat
ABSTRACT: Air quality in Kazakhstan cities has been poorly investigated despite their deteriorating situations. This study evaluates the national air pollution monitoring network data (PM10, NO2, SO2, and O3 ) in Kazakhstan cities, and provides the estimates of excess mortality rates associated with PM2.5 exposure using the Global Exposure Mortality Model (GEMM) concentration-response function. Morbidity rates associated with PM10 exposure were also estimated. Firstly, an air quality-based priority ranking of the cities was suggested based on the annual concentrations of the pollutants during the period of 3 years between 2015 and 2017. Nur-Sultan, Almaty, Ust-Kamenogorsk, and Aktobe were identified as the most polluted cities by PM10, NO2, SO2, and O3 respectively. Then, the exposure-response assessment was conducted for 21 cities. In major cities of Kazakhstan attributable to ambient air pollution per capita, mortality rate is 1 193 per 100 000 population per year, which is 8.97 times higher than in Europe. It is estimated that fine particulate matter exposure in the major cities of Kazakhstan causes 101 139 premature deaths annually. This study provides quantitative information on potential public health risks and impacts of air pollution, which is valuable for decision-makers to justify national environmental policies. Implications: Quantitative information on health impacts from air pollution can be useful for decision makers in Kazakhstan to justify environmental policies and identify policy and funding priorities for tackling air pollution issues. It can be also useful for policy makers in improving the quality of government funded environmental reports and strategic documents as they have many shortcomings in terms of selection of air quality indicators, identification of priority pollutants, identification of sources of pollution. This study has high significance due to the lack of data and knowledge in the region of Central Asia, in particular, of Kazakhstan.